Analysis of the internationalization and value chain activities in Chilean enterprises - Ana María Vallina-Hernández; Hanns de la Fuente-Mella; Rodrigo Fuentes-Solís (Contemporary Economics, 2022)
An open economy inserted in an environment with increasing participation of global value chains, such as the Chilean economy, requires information about how its business integrates into international markets. The contribution of this study is that it evaluates the stages and patterns of Chilean firms' internationalization by using a value chain activities framework, identifying four categories. The intensity of upstream and downstream business activities allows classifying the mode in each of the four categories. Members of the Sociedad de Fomento Fabril (SOFOFA) answered the survey design for this study. Results illustrate companies' behavior concerning international trade and foresight of further critical issues.
Keywords: F23; F14; M16; D22; 330; International Trade; Innovation; Latin American; Internationalization Strategy; Value Chain Activities